Development of Unity-based smart board Media to Improve Science and Social Studies Learning Outcomes - Liani, Sabrina Amanda; Tyas, Dewi Nilam (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
The low learning outcomes of students regarding the material on changes in the form of objects and the limited application of learning media are issues that need immediate attention in teaching Science and Social Studies Learning in elementary schools. This study aimed to develop and evaluate the feasibility and effectiveness of Unity-based smart board media to enhance the learning outcomes of grade IV Science and Social Studies Learning students regarding changes in the form of objects. Data were collected through observation, surveys, interviews, and documentation. Non-test techniques used in this study included interviews, observations, documentation, and questionnaires. The results indicated that the Unity-based smart board media met the eligibility standards, with media expert scores of 92.5% and material expert scores of 90.04%, indicating high feasibility. The fourth-grade teacher's response rate averaged 93.75%, and the student response rate averaged 94.79%, both of which are considered feasible. The t-test results showed a significance value (2-tailed) of 0.000, which indicates that Ha is accepted while Ho is rejected. The N-gain is 0.6536, which falls within the moderate criteria. Based on the study's results, it can be concluded that the developed Unity-based smart board media is feasible and effective for improving the learning outcomes of grade IV Science and Social Studies Learning regarding the material on changes in the form of objects, so that it can be a reference for teachers in designing interactive learning on various Science and Social Studies Learning materials, increasing student motivation and engagement in learning.